Silicon carbide ceramics: Mechanical activation, combustion and spark plasma sintering. Issue 11 (15th August 2016) - Moskovskikh, D.O.; Song, Y.; Rouvimov, S.; Rogachev, A.S.; Mukasyan, A.S.
Abstract: Single-stage fabrication of SiC ceramics by a combination of self-propagating high temperature synthesis (SHS) and spark plasma sintering (SPS) is reported. SHS+SPS is demonstrated to be an efficient method for production of SiC ceramics with density 3.1 g/cm 3, hardness of 24 GPa and toughness of 5 MPa m 1/2 . The starting material for the process is fine (50–300 nm in size) highly reactive powder, which involves composite particles of elemental carbon and silicon. This powder was prepared using a high-energy ball milling (HEBM). To optimize precursor preparation conditions, the structure transformation in nano-composite Si/C particles at different HEBM stages is also investigated.